Sustainable utilization of post-extraction residual biomass for solid biofuel production - Diana Kindzera; Viktoria Kochubei; Roman Hosovskyi (South African Journal of Chemical Engineering)
Post-extraction residual biomass, a by-product produced on an industrial scale following ethanol-water extraction of pelargonium (Pelargonium sidoides) tuberous roots, has been evaluated as a potential feedstock for solid biofuel production. To reduce the moisture content of biomass, the energy-efficient filtration drying method was used and pelargonium root (PR) test samples were prepared from the dried material. Comprehensive thermal analysis revealed that the thermal decomposition of the PR test samples occurred in four distinct stages, each characterized by specific temperature ranges and corresponding mass losses. The calorific value of the PR sample, determined via bomb calorimetry, was 19.3 MJ/kg. Considering the fixed carbon content of 20.6 %, the volatile matter content of 62.3 %, along with a favorable ash composition, but slightly elevated ash content of 5.1 wt.%, the dried post-extraction pelargonium root residual biomass can be recommended as feedstock for solid biofuel production when mixed with wood biomass.